How Research Skills Affect Indonesian Postgraduate Students Writing Outcomes: Publication Review - Sudarmo Sudarmo; Lusy Tunik Muharlisiani; Sardjana Orba Manullang; Erwinsyah Satria; Yeasy Agustina Sari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
This research reviewed how research skills affect the writing results of Indonesian postgraduate students. As academics have understood it. the success of studying at the postgraduate level was closely related to the skills and abilities to research various content and contexts of the field of study. The researchers have conducted a data collection series consisting of literature searching, observation, and documentation to prove this assumption. Furthermore, data was analyzed by defining the research question, collecting answers by sharpening the correlation and comparison between the questions and answers or findings. Finally, the researchers interpret in-depth whether the findings were valid and reliable. The design used phenomenology approach. Considering the data and the analysis results, the researchers conclude that the skills and abilities to research Indonesian postgraduate students greatly influence each writing or lecture assessment's quality or outcome, including research activities, final semester assignments, and weekly assignments. Therefore, the findings have a meaningful input for postgraduate students and policymakers for studying in master and undergraduate programs in Indonesia. Keywords: Research Skills, Writing Outcomes, Academic Study Review